(untitled) (Journal of Economic Research & Business Administration, 2018)
The article provides for the preconditions for the transition to a complex project management, covering all stages of the life cycle of innovative nanotechnologies in the field of nanotechnology. Structural relationships between nanotechnology routes are described, and the problem of control over the complexity of these relations is described. At the same time, the principles of project management in the field of nanotechnology are presented, which reflect the nature of these projects, their structure, other factors that determine participants and the specificity of managerial tasks. After defining the main features and perspectives of nanotechnology as a new technology, the document provides general risks associated with the use of nanotechnology and lack of risk management processes, as well as recommendations for governments, industries, international organizations and other stakeholders. The purpose of the research – The importance of nanoindustry in the country’s economy and the existence of a number of issues in this area require the elaboration of effective solutions for their effective solution to the transformation of the Nano-industrial complex of Kazakhstan. This article outlines one of the possible ways of transition to project management as an integrated management concept, which eliminates the problem of compatibility between the elements of the nanotechnology structure.